PENYULUHAN PENINGKATAN KUALITAS BELAJAR SISWA DALAM MENYONGSONG PEMBELAJARAN TATAP MUKA DI MASA PANDEMI DENGAN TETAP DISIPLIN DALAM MENERAPKAN PROTOKOL KESEHATAN DI YAYASAN PEMBANGUNAN MASYARAKAT SEJAHTERA (YPMS) DARUSSALAM KEDAUNG PAMULANG - M Anton Nurhidayat; Ading Sunarto; Lismiatun; Sam Cay; Dewi Sartika (Bajang Institute, 2021)
Learning is actually through the interaction of teachers with students to transmit knowledge in a learning environment. However, the dynamics of learning in Indonesia are currently being disrupted by the Covid-19 outbreak, which makes students have to undergo online learning activities. Many students experience difficulties and lack of motivation to participate in learning during the pandemic. One of the efforts to overcome educational problems during the pandemic is through learning assistance activities which are part of the Tridharma Perguruan Tinggi. This program is expected to help elementary school children in overcoming existing problems, so that children can understand and be motivated during online learning. The method used in this activity is the lecture method, discussion, and assignment method. The success of this activity can be seen from the enthusiasm and enthusiasm of students in participating in learning mentoring activities. In addition, students also succeeded in answering questions related to the material discussed.